2020
DOI: 10.1002/jcb.29711
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MALAT1 targeting miR‐124‐3p regulates DAPK1 expression contributes to cell apoptosis in Parkinson's Disease

Abstract: Death associated protein kinase 1 (DAPK1) was initially discovered in the progress of gamma-interferon induced programmed cell death, it is a key factor in the central nervous system, including Parkinson's disease (PD). However, the underlying mechanisms of DAPK1 in PD remain unclear and this research work aims to explore the potential mechanisms of DAPK1 in PD. In the study, we exposed SH-SY5Y cells to MPP + and treated mice with MPTP to investigate the roles of DAPK1 in PD and the underlying mechanisms. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 33 publications
(43 reference statements)
2
30
0
Order By: Relevance
“…lncRNA MALAT1 is highly expressed in PD as a ceRNA to regulate miRNA expression. e knockout of MALAT1 in mice inhibited the MPTPinduced apoptosis of dopaminergic neurons by upregulating miR-124 [31,34]. MALAT1/miR-205-5p axis regulates MPP(+)-induced apoptosis by targeting LRRK2 [33].…”
Section: Lncrnas and Apoptosis Of Dopaminergic Neurons In Pdmentioning
confidence: 99%
“…lncRNA MALAT1 is highly expressed in PD as a ceRNA to regulate miRNA expression. e knockout of MALAT1 in mice inhibited the MPTPinduced apoptosis of dopaminergic neurons by upregulating miR-124 [31,34]. MALAT1/miR-205-5p axis regulates MPP(+)-induced apoptosis by targeting LRRK2 [33].…”
Section: Lncrnas and Apoptosis Of Dopaminergic Neurons In Pdmentioning
confidence: 99%
“…LncRNA-p21 was shown to regulate the MPP-induced neuronal injury in SH-SY5Y cells via the miR-626-TRMP2 regulatory network [77]. MALAT1 acts as a mediator of cell apoptosis in PD mice and cellular models [129,130]. Further, the downregulation of lncRNA BACE1-AS in a PD rat model was reported to reduce the production of nitric oxide synthase, and thus, prevent oxidative stress [131].…”
Section: Functional Roles Of Lncrnas In Parkinson's Diseasementioning
confidence: 99%
“…Not only small ncRNAs but also long ncRNAs appear to be involved in brain-heart interactions. Indeed, a recent study showed that the lncRNA MALAT1 is a positive regulator of apoptosis and acts by inhibiting miR-124 levels in SH-SY5Y neuronal cell line and mice PD model [130]. MALAT1 is also known as a positive regulator of cardiomyocyte apoptosis and cardiac fibrosis [184,185].…”
Section: Non-coding Rnas In the Brain-heart Axis In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Further data showed that HOTAIR was upregulated in PD mouse model and improved the stability of LRRK2 mRNA by enhancing its expression and thus promoting the apoptosis of dopaminergic neurons [ 126 ]. Recently, it was also reported that the inhibition of lncRNA MALAT1 in PD mice induced the apoptosis of DA neurons by upregulating miR-124 [ 59 , 60 ]. Several studies have explored the potential of lncRNAs as attractive diagnostic and prognostic factors in neurodegenerative disease [ 127 ].…”
Section: Noncoding Rnas Regulatory Network In Neurological Diseasementioning
confidence: 99%